Technological development and universal basic income: from utopia to reality - Miladinovic, Slobodan M. (Sociološki pregled, 2022)
This paper analyzes the idea of universal basic income, which implies a periodic monetary payment received by all members of the society, with no prerequisites. Most former viewpoints contained numerous utopian elements. Therefore, the main aim of this paper is to point to the reality of this idea and answer the question whether it is yet another in a series of utopias, or there are actual foundations for its realization today. Modern technological development opens the space for increasing production by excluding human labour from it and by increasing profits of production organizers, whereas an increasing number of workers face temporary periods of unemployment during their working lives. All of the above make the idea of universal mandatory income up-to-date. The text explains the attitude that technological development, through mechanisms of profit redistribution, opens the space for this idea to overgrow its utopian character and become reality. The prerequisite is that the surplus of wealth that goes to production organizers should be redirected to the rest of the population.
Keywords: mandatory income; technological development; utopia; industrial society